2017
DOI: 10.3390/ijerph14090990
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Speciation and Extraction and the Significance of Biodegradable Acid on Arsenic Removal—An Approach for Remediation of Arsenic-Contaminated Soil

Abstract: A series of arsenic remediation tests were conducted using a washing method with biodegradable organic acids, including oxalic, citric and ascorbic acids. Approximately 80% of the arsenic in one sample was removed under the effect of the ascorbic and oxalic acid combination, which was roughly twice higher than the effectiveness of the ascorbic and citric acid combination under the same conditions. The soils treated using biodegradable acids had low remaining concentrations of arsenic that are primarily contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…Remediation methods to reduce the heavy-metal contents of DE by washing with water, citric acid solution, or EDTA solution significantly reduced iAs concentrations, with citric acid and EDTA being the most effective wash treatments (Figure ). Use of these treatments were selected on the basis of previous work indicating that EDTA and citric acid have the ability to chelate and solubilize heavy metals, possibly because their carboxylic acid functional groups chelate cations. Further, Van et al reported that organic acids are able to solubilize As­(III) and As­(V) in As-containing Fe oxides by chelating Fe 3+ counterions . Still, simply washing DE with water alone significantly reduced iAs concentrations.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Remediation methods to reduce the heavy-metal contents of DE by washing with water, citric acid solution, or EDTA solution significantly reduced iAs concentrations, with citric acid and EDTA being the most effective wash treatments (Figure ). Use of these treatments were selected on the basis of previous work indicating that EDTA and citric acid have the ability to chelate and solubilize heavy metals, possibly because their carboxylic acid functional groups chelate cations. Further, Van et al reported that organic acids are able to solubilize As­(III) and As­(V) in As-containing Fe oxides by chelating Fe 3+ counterions . Still, simply washing DE with water alone significantly reduced iAs concentrations.…”
Section: Discussionsupporting
confidence: 89%
“…37−40 Further, Van et al reported that organic acids are able to solubilize As(III) and As(V) in As-containing Fe oxides by chelating Fe 3+ counterions. 41 Still, simply washing DE with water alone significantly reduced iAs concentrations. The washing-treatment data indicate that a large fraction of the iAs in DE is highly soluble and thus can be removed from this filter aid by even a relatively short washing step.…”
Section: ■ Discussionmentioning
confidence: 99%
“…If the total As results (third column of Table 1 ) are compared with those of Table 2 , some deductions can be made. First of all, the difference between the sum of the fractions in Table 2 and the total content of As could be assimilated to the so-called “residual” As; i.e., the As that formed its own mineral species (see [ 26 ] for an exhaustive collection of As species in soils), or the As that was found as an impurity in the crystalline lattice of other non-arsenical mineral phases. In most samples, the residual As would represent more than half of the As content.…”
Section: Resultsmentioning
confidence: 99%
“…Most plants growing in soils polluted with toxic metals show a physiology in which they can avoid the uptake of metals, while in others, the accumulation process may differ between different parts of the plant. Mechanisms of toxic metal accumulation at the whole plant level involve the regulation of several processes, including metal uptake by the root [52]. Accumulation of toxic metals in plant roots can cause disturbances in the ratio of nutrients in plant tissues and changes in water balance [53].…”
Section: Evaluation Of the Accumulation Potential Of As And CD In The...mentioning
confidence: 99%